The design and modification of an experimental rig to test the erosion rate of duplex stainless steel S2507 in slurry - Tan, Sean Wei Long (2018)
This report will provide an in-depth insight into my final year project experience under the guidance of Professor Du Hejun and Dr Sun Zeqing. I will first provide a brief introduction about the project and then elaborate on the various experimental techniques and procedures that were carried out over the past year. This report will describe the 5 different setup that were made by a team of engineers which includes Dr Sun and me. The test will be carried out in water filled with sand and the impinging angle will be varied. Some tests were also performed in 3.5% salt water.